Transformasi Pembelajaran Al-Qur’an pada Anak Usia Dini melalui Penguatan Kompetensi Pedagogis Guru di Lembaga PAUD - Cicip Riyadi; Epy Pujiaty (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to analyze the transformation of Qur’anic learning in early childhood education through strengthening teachers’ pedagogical competence at Ma’had Tarbiyyah Al-Aulad Al-Manshurah Purbalingga. In this study, transformation refers to changes in teaching methods, learning media, and evaluation practices adapted to early childhood characteristics. This research employed a descriptive qualitative approach involving three teachers and 23 students. Data were collected through observation, interviews, and documentation. The findings show that strengthening teachers’ pedagogical competence leads to more varied teaching methods, such as integrating memorization with games and movement, the use of creative learning media including hijaiyah cards and visual aids, and more adaptive evaluation techniques based on observation and individual progress. These changes contribute to increased student engagement, improved recognition of hijaiyah letters, and the development of early religious habits. These findings indicate that pedagogical competence plays a crucial role in creating effective and developmentally appropriate Qur’anic learning in early childhood education.